Information and the nature of reality: from physics to metaphysics - Davies, Paul; Gregersen, Niels Henrik (Cambridge University Press, 2010)
"Many scientists regard mass and energy as the primary currency of nature. In recent years, however, the concept of information has gained importance. In this book, eminent scientists, philosophers, and theologians chart various aspects of information, from quantum information to biological and digital information, in order to understand how nature works. Beginning with a historical treatment of the topic, the book also examines physical and biological approaches to information, and the philosophical, theological, and ethical implications"--
Includes bibliographical references and index
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Konferenzschrift -- 2006 -- Kopenhagen; Natur; Materie; Wissenschaftsphilosophie; Information